Extended finite element method simulation and experimental test on failure behavior of defects under uniaxial compression. Issue 27 (14th December 2022) - Fu, Jinwei; Haeri, Hadi; Sarfarazi, Vahab; Asgari, Kaveh; Ebneabbasi, Pooyan; Fatehi Marji, Mohammad; Guo, Mengdi
Abstract: The conventional uniaxial compression test is used to investigate the interaction of two preexisting cracks with an internal hole in some typical gypsum specimens in the laboratory. The gypsum specimens are specially provided with 150 mm × 150 mm × 50 mm in dimensions and containing one internal hole and two cracks of 2 cm in lengths. These notches are located at varying distances, 2 cm, 3 cm and 4 cm from the hole and their inclination angles range from 0 to 90 degrees with an increment of 30 degrees. By this procedure, 12 different specimens can be provided for the experimental tests. On the other hand, an Extended Finite Element analysis of these tests is also provided in Abaqus software by assuming a plane strain state for the same specimens and taking the model geometry dimensions as 15 cm × 15 cm. In this analysis, the length of the cracks is 2 cm and their distances with the hole changes as 2 cm, 3 cm and 4 cm. However, in the two dimensional numerical simulation of the tests, the inclination angles of the cracks ranges from 0 to 90 degrees but the increment is taken as 15 degrees to provide 21 model samples and make a more detail analysis of the geo-mechanical problem. The results of laboratory tests and numerical models are very similar as far as the failure mechanisms and fracture patterns are conserened. The failure strengths are also very close for both analyses. It is concluded that the compressive strength of the specimens is highly affected by the fracture pattern and failure mechanism of the specimens assuming different configurations of the cracks and the hole locations.